Preference for Auditory Learning Style among University Students: A Comparative Study of Full-Time and Part-time Agricultural Education and Extension Students at Egerton University, Kenya - Kibet, Stella J.; Chepchieng, Micah C.; Makori, George; Chesaro, Daniel K. (American Journal of Education and Learning, 2019)
Understanding learning styles of students may help implement better teaching strategies resulting in higher quality of education. In Kenya, no conclusive research has been done on the preference of learning styles by university full-time and part-time students undertaking various degree programmes. This study, therefore, examined the preferred learning styles among full time and part time university students at Egerton University, Njoro Campus. The study utilizes the causal-comparative research design where 238 full-time and part-time students were selected through stratified random sampling from the population of 2nd, 3rd and 4th-year Agricultural Education and Extension students within Njoro campus. Purposive sampling was used to select six interview participants who were the class representatives. Data were collected by use of questionnaires which were administered to both full-time and part-time students and interviews were conducted among six class representatives Data analysis was done by use of descriptive and inferential statistics. Results showed that there was a statistically significant difference in the preference for auditory learning style between the full-time and part-time students, with the full time exhibiting a greater preference for auditory learning style than their counterparts. The full-time student further perceived installation of sound systems, frequent discussion of topical issues, and being given opportunities to ask questions as some of the aspects that were important to their learning. It was therefore concluded that the absence of auditory learning style in university education affects students effective learning especially the full-time ones. The university management in Kenya should, therefore, consider installing sound systems in lecture halls especially those used by full-time students in order to enhance their learning experience. Lecturers should also encourage classroom discussions and give opportunities for students to ask questions during lectures.